Fishing a floating port-a-cath fragment from the right heart chambers - Konstantinos Theodoropoulos; Konstantinos Tsakiridis; Antonios Kouparanis; Antonios Ziakas; George Kassimis (Advances in Interventional Cardiology, 2022)
We present the case of a 52-year-old man with pancreatic cancer who had a port-a-cath implanted for chemotherapy 4 years ago and was referred to our hospital for extraction. This was an incidental finding after a routine chest X-ray. The X-ray showed detachment of the distal port-a-cath fragment which had slipped in the right ventricle (Figure 1 A). A transthoracic echocardiogram demonstrated the detached fragment floating in the right ventricle and protruding in the right atrium through the tricuspid valve (Figure 1 B).